Towards a logology of law: The notion of “child” as a social construct - Léger-Riopel, Nicholas (Revue de l’Université de Moncton)

(untitled) (Revue de l’Université de Moncton, 2021)
Prompted by the work of Professor Lars Noah, this article presents logoly, the “science of sciences”, and potential uses for the legal discipline. Unburdened by any pretention to an “ontological” truth, legal notions, such as those relating to the field of Child Law, can be revisited in a new, more context-sensitive, way. A logology of legal notions reveal the deep dynamism and intersubjectivity present at their core: they are the product of contexts and of conflicts. While akin in this regard to sociology of knowledge, logology can also offer a “remedy” to latent positivism in Child Law. Thus, logology acts as a mean of protecting children and their rights.